2017
DOI: 10.4097/kjae.2017.70.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone on the onset time and recovery profiles of cisatracurium

Abstract: BackgroundThe effect of dexamethasone injection on cisatracurium-induced neuromuscular block was compared according to different injection time points.MethodsOne hundred seventeen patients were randomly assigned to three groups: 8 mg of dexamethasone injected intravenously 2–3 h before anesthesia (group A), just before anesthesia induction (group B), and at the end of surgery (control group). Three minutes after anesthesia induction, intubation was performed without neuromuscular blockers, and acceleromyograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(40 reference statements)
0
2
0
1
Order By: Relevance
“…Soltész et al 14 were the first to demonstrate that a single dose of intravenous dexamethasone can attenuate the duration of action of rocuronium. Another study reported a similar result with cisatracurium 15 . In both these trials, clinically relevant changes in the duration of action of neuromuscular blockers have only been seen when the dose was administered at least 2–3 h before induction.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Soltész et al 14 were the first to demonstrate that a single dose of intravenous dexamethasone can attenuate the duration of action of rocuronium. Another study reported a similar result with cisatracurium 15 . In both these trials, clinically relevant changes in the duration of action of neuromuscular blockers have only been seen when the dose was administered at least 2–3 h before induction.…”
Section: Introductionmentioning
confidence: 69%
“…Another study reported a similar result with cisatracurium. 15 In both these trials, clinically relevant changes in the duration of action of neuromuscular blockers have only been seen when the dose was administered at least 2-3 h before induction. However, in clinical practice, dexamethasone is commonly given only at induction.…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroizii au un mecanism direct de acțiune asupra axonilor nervilor motori, crescând sinteza de ACh și eliberarea spontană precum și stimulată de ACh, îmbunătățind astfel performanța musculară dar și prevenind blocul neuromuscular. Recuperarea blocului neuromuscular a fost accelerată când s-au administrat 8 mg dexametazonă cu 2-3 ore înainte de operație [22] sau chiar intraoperator [23].…”
Section: Rezultate șI Discuțiiunclassified